Numerical study on heat and flow transfer of biomagnetic fluid with copper nanoparticles over a linear extended sheet under the influence of magnetic dipole and thermal radiation - Murtaza, Mohammad Ghulam; Akter, Maria; Ferdows, Mohammad (Teknomekanik, 2023)
A steady, two-dimensional flow of biomagnetic fluid namely blood flow with copper nanoparticles across a stretchable sheet that is affected by a strong magnetic field and thermal radiation is investigated in this study. Copper nanoparticles (Cu-NPs) were used for this study because of their important applicability in biomedical research. Thus, the properties of copper nanoparticles render it an antibacterial, antimicrobial, and anti-fungal material. Similarity substitutions were applied to reduce the nonlinear partial differential equations to ordinary differential equations. Utilizing the MATLAB R2018b software bvp4c function technique, the physical solution was established. This model's pertinent dimensions, such as the ferromagnetic parameter, the magnetic field parameter, the radiation parameter, the suction parameter, the ratio parameter, the slip parameter, and the Prandtl Number, were computationally and graphically inspected about the dimensionless velocity, temperature, skin friction, and heat transfer rate. One of the pivotal observations was that a rise in the ferromagnetic parameter and Prandtl number drops the temperature and velocity, correspondingly. A cross-case analysis with the outcome of other published research is also executed for divergent parameter values. Based on the investigations, copper nanoparticles may be advantageous for biomedical purposes and lessen the hemodynamics of stenosis. Owing to the research, copper nanoparticle-concentrated blood exhibits a reduced flow impedance and a larger temperature changeability compared to sheer blood.